The Cognitive Behavior Counseling Guide Self Management Techniques to Increase the Self-Confidence of High School Students - Anak Agung Ayu Ngurah Catur Marta Paramita; Dewi Arum Widhiyanti Metra Putri (Bisma The Journal of Counseling, 2023)
The low level of student self-confidence is usually indicated by the attitude of students who do not dare to express opinions during learning. If this is allowed to continue, this will, of course, impact low student learning outcomes. This research aims to produce a cognitive behavior counseling guide product and self-management techniques to increase the self-confidence of Class X high school students. This research is classified as a development research developed using the 4D model. The subjects involved in this research were five experts. Data collection in this research was carried out using observation methods, interviews, and the distribution of questionnaires with research instruments in the form of questionnaires. The quality of the guidebook is tested using an acceptance test with guidance and counseling experts and testing the level of effectiveness with direct students. Acceptance testing uses the Lawshe formula by calculating CVR and CVI. The effectiveness test used the t-test using SPSS version 23. The results of the acceptance test showed that the level of suitability of the cognitive behavior counseling guidebook for self-management techniques to increase self-confidence in class X high school students was categorized as very suitable in terms of usefulness, accuracy, and feasibility. Meanwhile, the effectiveness test shows that implementing the cognitive behavior guidebook on self-management techniques effectively increases self-confidence in class X high school students. Based on the results of this analysis, it can be concluded that the cognitive behavior counseling guidebook can increase the self-confidence of class X high school students.